STUDI TENTANG PERSEPSI KUALITAS DAN KESADARAN MEREK SERTA DAMPAKNYA PADA LOYALITAS MEREK (Studi pada Konsumen AMDK Pelangi 600ml Kota Semarang) - Simbolon, Nathalia Rouli; Sukresna, I Made (Diponegoro Journal of Management, 2019)
Bottled drinking water is an alternative for people to get clean water easily. This opportunity makes the bottled water industry grow every year. Both the new brands and older brands adopted new strategies to get consumers' attention. Although many brands are rebranding and make an innovation in their products, the bottled water market is still dominated by big brand such as Aqua and Club with a gap that is quite far from its competing brands. One of growing brand of bottled water is Pelangi. This study discusses several factors such as packaging design, attitudes toward advertising, and perceived price and their effects on perceived quality and brand awareness and its impact on Pelangi’s brand loyalty.The population in this study were consumers of Rainbow AMDK in Semarang. The number of samples used was 156 people who were selected using purposive sampling through a questionnaire. Data obtained from questionnaires were then processed and analyzed using SPSS and AMOS programs.This study shows that there is a positive and significant influence between packaging design and perceived quality, between attitudes toward advertising and perceived quality, between attitudes toward advertising and brand awareness, between perceived price and perceived quality, and between price perceptions and awareness brand. In addition, there is also a positive and significant impact between perceived quality and brand loyalty, and between brand awareness and brand loyalty. As a result, companies can increase brand loyalty through a good attitudes towards advertising in the minds of consumers that will influence brand awareness and increase brand loyalty.